Novel serotonin transporter regulators: Natural aristolane- and nardosinane- types of sesquiterpenoids from Nardostachys chinensis Batal. Issue 1 (December 2017) - Chen, Ying-Peng; Ying, Shu-Song; Zheng, Hong-Hong; Liu, Yan-Ting; Wang, Zhong-Ping; Zhang, Hu; Deng, Xu; Wu, Yi-Jing; Gao, Xiu-Mei; Li, Tian-Xiang; Zhu, Yan; Xu, Yan-Tong; et al.
Abstract Serotonin transporter (SERT) is a classic target of drug discovery for neuropsychiatric and digestive disorders, and against those disorders, plants of Nardostachys genus have been valued for centuries in the systems of Traditional Chinese Medicine, Ayurvedic and Unani. Herein, chemical investigation on the roots and rhizomes ofNardostachys chinensis Batal. led to the isolation of forty sesquiterpenoids including six new aristolane-type sesquiterpenoids and six new nardosinane-type sesquiterprenoids. Their structures were elucidated by extensive spectroscopic methods, combined with analyses of circular dichroism and single-crystal X-ray diffraction data. To explore natural product scaffolds with SERT regulating activity, a high-content assay for measurement of SERT functionin vitro was conducted to evaluate the SERT regulating properties of these isolates. In conclusion, eleven compounds could be potential natural product scaffolds for developing drug candidates targeting SERT. Among which, kanshone C of aristolane-type sesquiterpenoid inhibited SERT most strongly, while desoxo-nachinol A of nardosinane-type sesquiterpenoid instead enhanced SERT potently.